If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2(4x + -3) = 138 Reorder the terms: 4x + 2(-3 + 4x) = 138 4x + (-3 * 2 + 4x * 2) = 138 4x + (-6 + 8x) = 138 Reorder the terms: -6 + 4x + 8x = 138 Combine like terms: 4x + 8x = 12x -6 + 12x = 138 Solving -6 + 12x = 138 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 12x = 138 + 6 Combine like terms: -6 + 6 = 0 0 + 12x = 138 + 6 12x = 138 + 6 Combine like terms: 138 + 6 = 144 12x = 144 Divide each side by '12'. x = 12 Simplifying x = 12
| K^2-3k-2=0 | | p(5)=3x^2+5x-4 | | 5x+9-4x=16 | | Y=ax-C | | 2(n-7)+3= | | 4f+8=8f-12 | | 2x-8x[9-4(x+3)]= | | 16t^2+12t^3=t^5 | | (6x+12)+(9x-4)= | | 50=7x-1 | | 4x+2+3x=2 | | -120-7+-120=-4([8*-10]+7)-11([-4*-10])+9 | | Pt-M^2t=P | | 3(4x-1)+2=2(2x-3) | | Or-M^2t=P | | 2(-7x-8)+12x=-1(-2x-8) | | 3x-1(x)=310 | | x+2ix-5=O | | 4(2b-3)=2(b-5) | | -1700x-10200=102000 | | -6x+3(-11x-7)=9-3(11x-8) | | .7y-1.5y=-35 | | 11x+3x=-9(x+9)+8(6x+7) | | -8+-6(-z+6)= | | 81x^2-5=139 | | 5r^2-2=403 | | 9p^2-1=899 | | 3(7+6u)+5u= | | 7m^2+12m+1=0 | | 4m^2-12=-8 | | x/2+3x/4=8 | | 6+10(5+10p)= |